The Association Between Chronotype and Physical Activity with Type of Obesity on Healthcare Students in Samarinda - Risda Septiana; Anik Lestari; Sapja Anantanyu (Journal of Health and Nutrition Research, 2026)
Obesity is a major global health problem, including in Indonesia, and is linked to increased risks of degenerative diseases and reduced quality of life. Based on the Asia-Pacific BMI classification from World Health Organization, Type I Obesity is defined as a BMI of 25–29.9 kg/m², while Type II Obesity (≥30 kg/m²) poses higher risks of degenerative diseases. In Indonesia, adult obesity prevalence has risen from 14.8% in 2013 to 23.4% in 2023, with East Kalimantan (29%) and Samarinda (25.9%) exceeding national averages. University students are a vulnerable group due to lifestyle transitions involving irregular sleep, dietary changes, and low physical activity. Among them, health sciences students hold a critical role in obesity prevention, yet their credibility may be challenged if they themselves engage in unhealthy behaviors. This study aims to determine the correlation between chronotype and physical activity with the type of obesity on healthcare students in Samarinda city. The research method used is quantitative with a cross-sectional study design. The study population consisted of 7,728 students from six universities with healthcare faculties in Samarinda City, from which a sample of 105 respondents was selected using a purposive sampling technique. Data collection was conducted using MEQ-SA and IPAQ-SF questionnaires. Data were analyzed using the logistic regression test. This study found a statistically significant relationship between physical activity and obesity type among healthcare students in Samarinda (p < 0.05). In contrast, no significant associations were observed between chronotype and obesity type (p > 0.05) on healthcare students in Samarinda.